2016
DOI: 10.1002/anie.201610916
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Capture from Ambient Air by Crystallization with a Guanidine Sorbent

Abstract: Carbon capture and storage is an important strategy for stabilizing the increasing concentration of atmospheric CO and the global temperature. A possible approach toward reversing this trend and decreasing the atmospheric CO concentration is to remove the CO directly from air (direct air capture). Herein we report a simple aqueous guanidine sorbent that captures CO from ambient air and binds it as a crystalline carbonate salt by guanidinium hydrogen bonding. The resulting solid has very low aqueous solubility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
103
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 106 publications
(108 citation statements)
references
References 28 publications
(36 reference statements)
4
103
0
1
Order By: Relevance
“…The reaction mixture was heated at 65 °C with mechanical stirring (350 rpm) for 4 h. The m-BBIG chloride salt (m-BBIGH2Cl2) formed as a solid suspension and the white crystalline product was collected by vacuum filtration and washed with ethanol followed by diethyl ether, then allowed to dry for a few hours. The yield of m-BBIGH2Cl2 was 228.92 g (96% obtained by this method was lower than the corresponding yield of the PyBIG analog [24] due to the significantly higher solubility of m-BBIG (50 mM) compared to PyBIG (10 mM). The solid cake of m-BBIG carbonate was transferred to a large crystallization dish, breaking it up and spreading it into a thin layer.…”
Section: Synthesis Of M-bbigmentioning
confidence: 73%
See 1 more Smart Citation
“…The reaction mixture was heated at 65 °C with mechanical stirring (350 rpm) for 4 h. The m-BBIG chloride salt (m-BBIGH2Cl2) formed as a solid suspension and the white crystalline product was collected by vacuum filtration and washed with ethanol followed by diethyl ether, then allowed to dry for a few hours. The yield of m-BBIGH2Cl2 was 228.92 g (96% obtained by this method was lower than the corresponding yield of the PyBIG analog [24] due to the significantly higher solubility of m-BBIG (50 mM) compared to PyBIG (10 mM). The solid cake of m-BBIG carbonate was transferred to a large crystallization dish, breaking it up and spreading it into a thin layer.…”
Section: Synthesis Of M-bbigmentioning
confidence: 73%
“…Following the proof of principle with PyBIG [23][24][25], we now seek to establish the generality of the amino acid/BIG approach to DAC. One advantage of the BIG family of compounds is that their syntheses are straightforward and modular, consisting of imine condensation of aminoguanidinium salts with different dialdehydes [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of PyBIG carbonate was reported previously (Seipp et al, 2017;Brethomé et al, 2018) and we have preserved the setting of the unit cell and the atom numbering used in that work. Based on our experimental neutron data, the crystal structure was re-refined within the SHELXTL program suite (Sheldrick, 2015) using the previously reported structure as the starting model.…”
Section: Refinementsmentioning
confidence: 99%
“…The previously reported X-ray crystal structure of (PyBIGH 2 )(CO 3 )(H 2 O) 4 showed that the hydrated carbonate salt comprises an elaborate hydrogen-bonded network involving the carbonate anion, guanidinium cations, water molecules and the pyridine N atom (Seipp et al, 2017;Brethomé et al, 2018). However, the precise geometrical parameters and energetics of the hydrogen bonds and other intermolecular interactions present in this structure, which presumably play important roles in the unusually low aqueous solubility of (PyBIGH 2 )(CO 3 )(H 2 O) 4 , have yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation